Professional Development of Functional Positions of Education Personnel at State University of Surabaya Towards a Legal Entity State University (PTNBH) - Suprapto,; Sarmini,; Setiawan, Slamet; Ariningrum, Desrina; El Rizaq, Agung Dwi Bahtiar; Suci Ulamatullah, Tri (The Indonesian Journal of Social Studies, 2022)
Professional development of functional positions of education staff at the State University of Surabaya to State Universities with Legal Entities ( PTNBH ) are important studies considering that the output is Unesa's HR in accordance with the mandate of the Statute and UNESA's SOTK as PTNBH. Meanwhile, the objective of this research is to analyze the needs and professional development of the functional positions of educational staff needed in accordance with SOTK UNESA PTNBH. This study uses a quantitative approach with a descriptive method. Data collection techniques are through questionnaires, FGDs, and workshops. The data were analyzed using statistical techniques with the SPSS program, qualitative analysis, and pattern analysis to formulate conclusions and formulate recommendations. The results of this study show; (1) it is necessary to increase the understanding of the Permenpan RB which regulates the functional positions; (2) most of them require training in the preparation of research proposals, writing scientific papers for translation and adaptation of books, in order to fulfill the components of professional development credit properly; (3) most have not had the opportunity to participate in research from the institution. There is great hope for them, the institution has a policy in research management; (4) some of them have assignments that are not in accordance with their functional positions, so this makes it difficult for them to fulfill professional development credit scores.